2021
DOI: 10.1111/cns.13699
|View full text |Cite
|
Sign up to set email alerts
|

AIM2 deletion enhances blood‐brain barrier integrity in experimental ischemic stroke

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 41 publications
(95 reference statements)
0
36
0
Order By: Relevance
“…Furthermore, the exact molecular mechanisms of neuronal ferroptosis caused by accumulated cerebral FA needs to be further studied. Apart from formaldehyde accumulation, other mechanisms such as blood brain barrier damage, 48,49 oxidative stress, 50 excessive mitophagy and neuroinflammation, 51 may also impair neurological function in hypoxia conditions and need to be further explored. Last, only male mice were used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the exact molecular mechanisms of neuronal ferroptosis caused by accumulated cerebral FA needs to be further studied. Apart from formaldehyde accumulation, other mechanisms such as blood brain barrier damage, 48,49 oxidative stress, 50 excessive mitophagy and neuroinflammation, 51 may also impair neurological function in hypoxia conditions and need to be further explored. Last, only male mice were used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, mitochondrion is an organelle that plays roles in energy conversion and metabolism, and its dysfunction is the crucial pathophysiological change in ischemic stroke due to oxygen-glucose deprivation ( 14 ). It was found that a few studies have confirmed that NLRC4 ( 15 ), NLRP1 ( 16 ) and AIM2 ( 17 ) can promote cerebral ischemic injury, but there is no evidence that mitochondria can affect the pathological process of cerebral ischemia through them. Previous studies revealed that mitochondrial dysfunction is a vital event during the NLPR3 inflammasome activation ( 18 - 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wang's study showed that MiR‐30a inhibitor restored the loss of occludin in microvessels of ischemic stroke rats and attenuate BBB breakdown and ischemic infarction, which conduced better outcome 26 . Xu's study also showed that ischemic reperfusion injury significantly decreased those of the tight junction (TJ) proteins occludin and ZO‐1, and AIM2 knockdown effectively protected BBB integrity by promoting the expression of occludin and ZO‐1 proteins, 27 and Izawa et al. suggested that inter‐endothelial claudin‐5 expression significantly decreased when β1‐integrin–collagen IV interactions were interrupted and subsequently extended the observations to the loss of ZO‐1 and of occludin at the inter‐endothelial interface, ultimately increasing BBB permeability 28 …”
Section: Discussionmentioning
confidence: 98%
“…Wang's study showed that MiR-30a inhibitor restored the loss of occludin in microvessels of ischemic stroke rats and attenuate BBB breakdown and ischemic infarction, which conduced better outcome. 26 Xu's study also showed that ischemic reperfusion injury significantly decreased those of the tight junction (TJ) proteins occludin and ZO-1, and AIM2 knockdown effectively protected BBB integrity by promoting the expression of occludin and ZO-1 proteins, 27 b Core infarct volume was estimated by CT perfusion imaging. For baseline CT perfusion imaging, thirteen patients were obtained in the END group; 45 were obtained in the non-END group.…”
Section: Discussionmentioning
confidence: 99%